The Opportunity to Live Well: The Wisdom of Nelson Mandela, Gough Whitlam, Pete Seeger and Others - James, Paul (Cambridge Scholars Publishing, 2017)
What is the greatest, most precious, opportunity that life provides? It is not winning millions in a lottery. Money, fame, intelligence, beauty, a prestigious career, or mere existence will not simply provide us with a good life. We all have the potential to live well, to have a good life, but how can we do so? We can master complex subjects, attain advanced qualifications and demonstrate sound skills; we can become wealthy, and still make a mess of our lives. People can meet the accepted measures of success, yet still not live well. Gough Whitlam, Nelson Mandela, Pete Seeger, Luke Kelly and Ben of Kombi Life are used here to demonstrate the challenges and joyous rewards of living well. They inform, and teach us, that we can also live well when we cultivate awareness; altruism; wholeness of body, mind and spirit; resilience and persistence; passion; empathy; a sense of belonging; personal character; self-knowledge; and life-enhancing habits.